Synthesis of Lead-Free Perovskite Films by Combinatorial Evaporation: Fast Processes for Screening Different Precursor Combinations - Wong, Man Kwong; Liu, Fangzhou; Kam, Chun Sing; Leung, Tik Lun; Tam, Ho Won; Djurišić, Aleksandra B; Popović, Jasminka; Li, Hangkong; Shih, Kaimin; Low, Kam-Hung; Chan, Wai Kin; Chen, Wei; et al. (Chemistry of materials, 2017)
We demonstrate an evaporation-based combinatorial approach for fast screening of precursor combinations for the synthesis of novel perovskite materials. Nine material combinations can be explored simultaneously, which enabled us to synthesize nine different lead-free perovskite compounds. The structural properties (morphology, crystal structure) and optical properties (UV–vis absorption spectra, photoluminescence) of the prepared materials were investigated. Among these materials, several Sn-based and Pd-based perovskites exhibit strong absorption in the visible spectral range and thus may be of interest for photovoltaic applications. In addition, butyl ammonium tin iodide exhibits bright red emission, and it is of interest for potential light emitting applications.